miR-429-3p/LPIN1 Axis Promotes Chicken Abdominal Fat Deposition via PPARγ Pathway - Chao, Xiaohuan; Guo, Lijin; Wang, Qi; Huang, Weiling; Liu, Manqing; Luan, Kang; Jiang, Jinqi; Lin, Shudai; Nie, Qinghua; Luo, Wen; Zhang, Xiquan; Luo, Qingbin (Frontiers in Cell and Developmental Biology, 2020)
To explore the regulatory mechanism of abdominal fat deposition in broilers, 100-day-old Sanhuang chickens (n=12) were divided into high-fat and low-fat groups, according to the abdominal fat ratio size. Total RNA isolated from the 12 abdominal fat tissues was used for miRNA and mRNA sequencing. Results of miRNA and mRNA sequencing revealed that miR-429-3p was highly expressed in high-fat chicken whereas LPIN1 expression was downregulated. Further, we determined that miR-429-3p promoted preadipocyte proliferation and differentiation, whereas LPIN1 exerted an opposite effect. Notably, we found that the miR-429-3p/LPIN1 axis facilitated PPARγ pathway activation, which is closely associated with the progression of adipogenesis. In conclusion, our results provide evidence that a novel miR-429-3p/LPIN1 axis is involved in the regulation of adipogenesis, which may have a guiding role in the improvement of breeding for abdominal fat traits in broiler chickens.